Environmental association modelling with loci under divergent selection predicts the distribution range of a lizard. Issue 15 (16th June 2021) - Llanos‐Garrido, Alejandro; Briega‐Álvarez, Andrea; Pérez‐Tris, Javier; Díaz, José A.
Abstract: During the historical building of a species range, individual colonizers have to confront different ecological challenges, and the capacity of the species to broaden its range may depend on the total amount of adaptive genetic variation supplied by evolution. We set out to increase our understanding of what defines a range and the role of underlying genetics by trying to predict an entire species' range from the geographical distribution of its genetic diversity under selection. We sampled five populations of the western Mediterranean lizard Psammodromus algirus that inhabit a noticeable environmental gradient of temperature and precipitation. We correlated the genotypes of 95 individuals (18–20 individuals per population) for 21 SNPs putatively under selection with environmental scores on a bioclimatic gradient, using 1 × 1 km 2  grid cells as sampling units. By extrapolating the resulting model to all possible combinations of alleles, we inferred all the geographic cells that were theoretically suitable for a given amount of genetic variance under selection. The inferred distribution range overlapped to a large extent with the realized range of the species (77.46% of overlap), including an accurate prediction of internal gaps and range borders. Our results suggest an adaptability threshold determined by the amount of genetic variation available that would be required to warrant adaptation beyond a certain limit of environmental variation. These results support the idea that the expansion of a species' range can be ultimately linked to the arising of new variants under selection (either newly selected variants from standing genetic variation or innovative mutations under selection).